PENGARUH KEPERCAYAAN KONSUMEN DAN KEMUDAHAN PENGGUNAAN APLIKASI TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP SHOPEE (Studi Kasus pada Mahasiswa Ilmu Administrasi Bisnis Institut Ilmu Sosial dan Manajemen STIAMI di Jakarta) - Aisyah Aisyah; Yayak Heriyanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This thesis used a quantitative study on the influence of consumer trust and easiness to use an application on purchasing decision in shoppee online shop to Students of Business Administration Science of Social and Management Science of STIAMI in Jakarta. In this study, multiple linear regression analysis using f and t tests was used. Samples were determined using purposive sampling technique. The amount of sample in this study was 53 students based on online transaction activities via shopee online shop. This study used two variables, namely dependent and independent variables. The dependent variable is purchasing decision, while the independent variable includes Consumer Trust (X1) and Easiness to Use an Application (X2). The result of simultaneous regression coefficient testing was that Fcal of 24.029 Ftable of 3.18, thus the consument trust and easiness to use an application simultaneously influenced the purchasing decision. In partial t test statitistic testing was obtained consumer trust variable of Fcal of 6.860 and easiness to use an application variable Ftable of 1.675, which means each independent variable influences the dependent variable partially.s.